The Hurricane Express [videorecording (DVD)] : [a thriller of the roaring rails in 12 chapters] - Shaefer, Armand; McGowan, J. P. (John P.), 1880-1952; Wayne, John, 1907-1979; Marshall, Tully, 1864-1943; Tearle, Conway, 1878-1938; Strange, Glenn, 1899-1973 (Classic movie serials., 2006)
John Wayne plays Larry Baker, an air freight pilot whose father is the engineer on the Hurricane Express. When a train collision kills his father, Baker must determine who caused the wreck.